Terrestrial biomarker results from IODP Site 356-U1461 over the last 5 million years - Yuxin He; Huanye Wang (PANGAEA, 2024)
This dataset presents biomarker-based records of terrestrial input to the northwest shelf of Australia over the last 5 million years, based on sedimentary core from IODP Site U1461. The biomarkers include ratio of n-C31 alkane over C28–30 sterols, brGDGT-based proxies, and δ13Corg. These records would eventually provide a framework of terrestrial input in many perspectives. We aim to disentangle the response of vegetation and dust transportation to climate variations in the northwestern Australian continent through the Pliocene-Pleistocene period.